1996
DOI: 10.1002/bjs.1800830835
|View full text |Cite
|
Sign up to set email alerts
|

Food intake after gastrectomy for gastric carcinoma: The role of a gastric reservoir

Abstract: Patients with carcinoma of the stomach who underwent curative resection were randomized to total gastrectomy (n = 49), total gastrectomy and an S-shaped gastric substitute (n = 28) or subtotal gastrectomy (n = 12); all had a Roux-en-Y reconstruction. The gastric substitute and gastric remnant allowed a volume of 400-500 ml to be installed without increments in basal pressures. The corresponding volume in the Roux limb was 100 ml. Energy intake was approximately 120 kJ/kg preoperative weight per day 3 months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1
12

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 21 publications
6
64
1
12
Order By: Relevance
“…The smaller pouches (5 and 10 cm) were unable to achieve such volumes at basal and intermediate pressures, i.e., pressures that would be tolerated by patients without experiencing satiety. With the smaller pouches, in excess of 350 ml was only attainable with distending pressures of 45 cmH 2 O, at which stage patients would experience troublesome symptoms such as epigastric pain, nausea, and vomiting, in accordance with work carried out by Liedman et al [18]. However, the larger pouches (15 and 20 cm) achieved the desired volume at basal and intermediate pressures which could be tolerated by patients without adverse side effects.…”
Section: In Vitro Assessment Of Pouchessupporting
confidence: 75%
See 1 more Smart Citation
“…The smaller pouches (5 and 10 cm) were unable to achieve such volumes at basal and intermediate pressures, i.e., pressures that would be tolerated by patients without experiencing satiety. With the smaller pouches, in excess of 350 ml was only attainable with distending pressures of 45 cmH 2 O, at which stage patients would experience troublesome symptoms such as epigastric pain, nausea, and vomiting, in accordance with work carried out by Liedman et al [18]. However, the larger pouches (15 and 20 cm) achieved the desired volume at basal and intermediate pressures which could be tolerated by patients without adverse side effects.…”
Section: In Vitro Assessment Of Pouchessupporting
confidence: 75%
“…Liedman et al [18] demonstrated that intragastric/pouch pressures approaching 15 cmH 2 O were tolerated by patients without experiencing symptoms of satiety; whereas higher pressures approaching 45 cmH 2 O were poorly tolerated by patients, resulting in epigastric pain, nausea, and vomiting. An average meal size in elderly patients equates to 350-400 ml, according to data gathered from our unit.…”
Section: In Vitro Assessment Of Pouchesmentioning
confidence: 99%
“…One could expect that after total gastrectomy, loss of the gastric reservoir reduces calorie intake, which is a major cause of weight loss (Liedman et al, 1996). However, after subtotal gastrectomy, no significant difference in food intake was found preoperatively and 1 year after surgery.…”
Section: Jeon Et Al 2004mentioning
confidence: 99%
“…Randomized studies published in this fi eld mainly question the importance of reservoir construction [1,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]; fewer trials research the importance of duodenal passage preservation [11,14,[23][24][25][26]. Two expert reviews have been published, each trying to draw evidence-based conclusions by means of a metaanalysis of all available randomized trials [27,28].…”
Section: Discussionmentioning
confidence: 99%